Monitoring and Controlling The Hybrid System Using The Internet Of Things For Energy Transaction - Wibowo, Sulton Ari; Lestari, Dyah (Frontier Energy System and Power Engineering, 2019)
The electrical energy is an energy that is needed by the people. Theelectrical energy, to date, came from several power plants, such aselectric steam power plants and diesel power plants. The communitymust pay the service provider, such as the State ElectricityCompany (PLN) with a rising cost, to obtain electrical energy.However, there were other alternative energies, for example, solarpower plants and windmill power plants. The hybrid system is acombination of two or more different energy sources to meet thedemand. The hybrid system was also expected to solve the problemthat might arise in utilizing other energies, the site condition, andthe unpredicted situation on the power plant. The solution to theseproblems was a hybrid using a monitoring device with ACS 712sensor current parameter, ZMPT101B voltage sensor, LDR solarsensor, hybrid electrical energy power, controller for four electricalsource inputs and three electrical sources for the output load. Thedevice used Arduino Mega 2560 for data processing, ESP 8266 asthe module to connect the device to the internet network and relayas the control actuator. Monitoring and controlling the device usedthe internet network and the implementation of the Internet ofThings (IoT) on the hybrid system plants (PLN, generator, solarpower plant, windmill power plant) that was integrated into thewebsite. The overall test resulted in the comparison average errorvalue between the device and the measuring instrument of thecurrent, voltage, and power. The test also resulted in the averageerror value of the response time for the four input contacts and threeoutput contacts. The average error value of the current was 2.13%,the average error value of the voltage was 0.7%, and the averageerror value from the power parameter was 0%. Meanwhile, theaverage error value of response time was 0.23 seconds. Based onthe above results, it can be concluded that the monitoring andcontrolling system from the website with the implementation of theIoT in the hybrid power system was worked following the design.